High-Order Laplacian Regularized Low-Rank Representation for Multimodal Dementia Diagnosis - Dong, Aimei; Li, Zhigang; Wang, Mingliang; Shen, Dinggang; Liu, Mingxia (Frontiers in Neuroscience, 2021)
Multimodal heterogeneous data, such as structural magnetic resonance imaging (MRI), positron emission tomography (PET), and cerebrospinal fluid (CSF), are effective in improving the performance of automated dementia diagnosis, by providing complementary information on degenerated brain disorders, such as Alzheimer's prodromal stage, \ie, mild cognitive impairment (MCI). Effectively integrating multimodal data has remained a challenging problem, especially when these heterogeneous data are incomplete due to poor data quality and patient dropout. Besides, multimodal data usually contain noise information caused by different scanners or imaging protocols. The existing methods usually fail to well handle these heterogeneous and noisy multimodal data for automated brain dementia diagnosis. To this end, we propose a high-order Laplacian regularized Low-Rank Representation (hLRR) method for dementia diagnosis using block-wise missing multimodal data. The proposed method was evaluated on 805 subjects (with incomplete MRI, PET and CSF data) from the real Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort. Experimental results suggest the effectiveness of our method in three tasks of brain disease classification, compared with the state-of-the-art methods.